Nature Conservation as a Core Pillar: Strategies for Developing Educational Tourism in Pulau Untung Jawa Towards Sustainable Tourism: Nature Conservation as a Core Pillar: Strategies for Developing Educational Tourism in Pulau Untung Jawa Towards Sustainable Tourism - Rilla Rianty; Maidar Simanihuruk; Pipin Noviati Sadikin; Diah Renata Anggraeni (Bogor Hospitality Journal, 2024)
TThe COVID-19 pandemic has shifted tourists' preferences toward quality tourism that emphasizes nature-based experiences. This study proposes development strategies for conservation-based educational tourism in Pulau Untung Jawa Tourism Village, located in Kepulauan Seribu, DKI Jakarta Province. Using a numerical SWOT approach through IFAS and EFAS analyses, the study identifies the destination's strengths, weaknesses, opportunities, and threats. The analysis results highlight that Pulau Untung Jawa possesses a strong foundation for conservation-based development, with notable strengths such as abundant natural resources, active community involvement, and the availability of educational tourism packages. However, weaknesses in infrastructure and supporting facilities require immediate attention. The EFAS analysis identifies significant opportunities to foster collaboration between the government and local communities, alongside providing training and incentives to enhance community capacity. Conversely, digitalization trends and the socio-environmental impacts of tourism activities are recognized as major threats. Based on the IE matrix and SPACE diagram analyses, Pulau Untung Jawa is strategically positioned for aggressive growth and development. Strategic recommendations include enhancing digital marketing, diversifying educational tourism products, investing in eco-friendly infrastructure, strengthening local human resource capacity, and fostering sustainable multi-stakeholder collaboration. Implementing these comprehensive strategies could position Pulau Untung Jawa as a leading model for conservation-based tourism villages, delivering economic benefits while preserving cultural heritage and protecting the environment